Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kemiskinan Antar Provinsi di Indonesia Tahun 2018–2024 - Nabila Amarah Dani; Hanasya Putri Hanafi; Destri Hamidah; Yossinomita Yossinomita (Prosiding Seminar Nasional Ilmu Teknik, 2025)
The purpose of this study is to investigate the factors that lead to poverty in different Indonesian regions between 2018 up to 2024. The Gross Regional Domestic Product per capita, the Human Development Index, and the Open Unemployment Rate are the independent factors used in this study, whereas poverty levels are the dependent variable. The Central Statistics Agency provided secondary data that was used in a quantitative manner. Using EViews 12 software, panel regression techniques were used to process the data. The study's conclusions show that, at a significance level of less than 0.05, economic and human development factors simultaneously significantly affect poverty rates across Indonesian regions. The coefficient of determination indicates that the variables in the model can account for the majority of the variations in poverty levels. These findings demonstrate how important a region's economic status and level of human development are to efforts to reduce poverty. It is anticipated that this research will help the government develop more effective and long-lasting methods for reducing poverty.